Optimizing agricultural demand for reducing costs of renewable energy integration - Tarun Khanna (ZBW - Leibniz Information Centre for Economics, 2021)
While demand response is recognized as a useful tool in reducing costs of integrating renewable electricity, the related literature in developing countries has been limited due to lack of data on end use load profiles. Meanwhile, while the water-energy-nexus is well researched, the value of agricultural pumping load as a demand side resource is ignored. This article fills these gaps by using agricultural load data from two distribution utilities in the Indian state of Gujarat and a mixed integer cost optimization model to estimate the reduction in renewable integration costs using agricultural demand response. We estimate that agricultural load management reduces total system costs by 5% in the current system. Going forward, profile costs of integrating 50% VRE are estimated at 33/MWhVRE. Agriculture demand management can reduce these costs by 24%, by reducing renewables curtailment by 4-7% and improving system flexibility. Deploying decentralized solar irrigation pumps instead of large-scale solar power plants enables higher absorption of peak solar generation and reduces costs further. We conclude that in power systems with moderate share of pumping load, agricultural demand response can be a low-cost tool for renewables integration. Where these costs are disproportionately borne by end consumers, it also has significant consumer welfare effects.
More recent version: http://hdl.handle.net/10419/235858
Keywords: 330; renewables integration; demand response; energy water nexus